Analisis Pengaruh Risiko Suku Bunga Bank Indonesia dan Net Interest Margin terhadap Profitabilitas Bank Konvensional di Indonesia - Rinka Az- Zahra; Irvan Yoga Pardistya (STIE AMKOP, 2022)
Banks face various risks that can become barriers to increasing profitability. There are two factors that affect the profitability of a bank, namely internal and external factors. Internal factors are measured using financial ratios by analyzing the financial statements presented by the bank and one way is by examining the Net Interest Margin (NIM). Meanwhile, external factors are factors outside the company originating from macroeconomics, including the risk of Bank Indonesia interest rates. Banking was chosen in this study because banking activities are very influential for the smooth running of the real sector economy. This research is devoted to its profitability because profitability is an important factor in banking development. This study aims to determine the effect of BI interest rate risk, Net Interest Margin (NIM) partially and simultaneously on profitability as indicated by the ROA (Return to Assets) ratio using the classical assumption test and multiple regression test of conventional banks listed on the Indonesia Stock Exchange. 2012-2019 period. This type of research is a descriptive study with secondary data derived from registered financial statements of conventional banks and obtained directly from the website at the Financial Services Authority. This study uses data from 2012-2019 with a sample size of 4 conventional banks from a total population of 45 conventional banks. The results of this study indicate that; 1) BI interest rate risk does not partially affect profitability; 2) Partially Net Interest Margin has a negative effect on profitability; and 3) BI interest rate risk and Net Interest Margin have a positive effect on profitability. Keywords: BI Interest Rate Risk, Net Interest Margin, Profitability, Return On Assets.